Analisis Dampak Faktor Ekonomi Orang Tua di Masa Pandemi Covid 19 dengan Minat Kuliah ke Perguruan Tinggi - Basuki; Jatmoko, Dwi; Purwanto, Joko; Nurhidayati; Fajar Isbakhi, Ari (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This study aims to describe: analysis of the impact of economic factors on parents with an interest in continuing their studies to college. The subjects of this study were students of class XII SMA/K throughout Purworejo Regency for the Academic Year 2021/2022. This research is a population study, so that all students of class XII are randomly assigned with a total of 100 students as research samples. The research design used is Ex-Post Facto because in this study the data obtained are data from the results of events that have taken place. The variable in this study is the parents' economy (X) while the independent variable is the interest in continuing their studies to college (Y). The technique of collecting data for parents' economic status and interest in continuing their studies in higher education is done by using technical technical questionnaires. The results showed that there was a positive relationship between the social status of students' parents and their interest in continuing their studies to class XII SMA/K in Purworejo district for the academic year 2021/2022 as indicated by a correlation coefficient of 0.285. There are many things that influence students' interest in continuing their studies to college, but this study only involved one independent variable, namely the socioeconomic status of parents. From this, it is realized that there are many other factors during the COVID-19 pandemic that affect interest in continuing their studies to college.